2022
DOI: 10.1111/jvh.13721
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic carcinogenicity of oral nucleos(t)ide analogues in chronic hepatitis B carriers: A 35,000‐Korean outcome study

Abstract: Evidence on the carcinogenicity of oral nucleos(t)ide analogues (NAs) is inconclusive and lacks data on the effects by chemical structure of the NAs in patients with chronic hepatitis B (CHB). We aimed to provide definitive results on this issue using a large set of CHB patients and data on all major NA drugs. The study population consisted of 10,331 patients with CHB receiving primary NA treatment for more than 6 months, and 24,836 untreated controls followed for at least as long as the treated patients.Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, the underlying molecular mechanisms in HBV-induced colorectal cancer remain unknown. Furthermore, recent evidence demonstrated that anti-virus treatments in chronic HBV infection patients also increased the colorectal cancer risk (81). Accordingly, future analyses should consider this confounding information.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…However, the underlying molecular mechanisms in HBV-induced colorectal cancer remain unknown. Furthermore, recent evidence demonstrated that anti-virus treatments in chronic HBV infection patients also increased the colorectal cancer risk (81). Accordingly, future analyses should consider this confounding information.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…While such inhibitors may help to decrease high rates of soL1R in CRC, they could also downplay innate immune recognition and elimination of early neoplastic lesions, a concept recently dubbed the “fire alarm” hypothesis [ 18 ]. In this regard, Hepatitis B patients from a large cohort study (>35,000 individuals) undergoing long-term RT inhibitor treatments showed increased CRC incidence compared to untreated subjects [ 19 ]. It would be interesting to determine whether treated patients were more prone to immune evasion by early CRC lesions due to reduced production of LINE1 ORF2-dependent double-stranded nucleic acid species.…”
Section: Main Textmentioning
confidence: 99%